2009
DOI: 10.1007/s11661-008-9749-1
|View full text |Cite
|
Sign up to set email alerts
|

Hot Ductility of Nb- and Ti-Bearing Microalloyed Steels and the Influence of Thermal History

Abstract: The hot ductility of Nb, Ti, and Nb-Ti containing steels has been studied under direct-cast conditions. A Gleeble 3500 thermomechanical simulator was used to determine hot ductility over the temperature range 1100°C to 700°C at a low strain rate of 7.5 9 10 À4 s À1 . Tensile samples were cooled at two different cooling rates, 100°C/min and 200°C/min, simulating, respectively, thick and thin slab casting processes. Complex thermal patterns designed to simulate the cooling conditions experienced near the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 22 publications
(40 reference statements)
0
24
0
1
Order By: Relevance
“…The observed facet grain surfaces with shallow dimples are characteristics of failure due to GBS, i.e., intergranular decohesion. Similarly, in C-Mn-Nb steel, Carpenter et al [25] found that the fracture surfaces obtained from hot tensile specimens tested in the single phase austenite region exhibited intergranular decohesion, displaying facet, due to the GBS.…”
Section: Voidmentioning
confidence: 92%
“…The observed facet grain surfaces with shallow dimples are characteristics of failure due to GBS, i.e., intergranular decohesion. Similarly, in C-Mn-Nb steel, Carpenter et al [25] found that the fracture surfaces obtained from hot tensile specimens tested in the single phase austenite region exhibited intergranular decohesion, displaying facet, due to the GBS.…”
Section: Voidmentioning
confidence: 92%
“…Specimens are then heated slowly up to the temperature which melting occur and were held at this temperature for 60 s to heat the middle zone of specimens homogenously. A small amount of compressive deformation (2% to 10%) [7,20,21] is axially applied onto the specimens during first solidification step through to 1380 °C to be able to eliminate the shrinkage. Approximately 2% compressive strain was applied to the specimens in these tests.…”
Section: Methodsmentioning
confidence: 99%
“…The fracture surface of the as-annealed specimen is the typical feature of ductile fracture by the presence of isometric dimples (Figure 5a). Furthermore, there are some flat regions marked with white arrows in Figure 5d, indicating failure due to grain boundary sliding in the 55% condition [32]. The corresponding dimple diameter distribution of samples at different rolling reductions is depicted in Figure 5e.…”
Section: Fractographic Featuresmentioning
confidence: 96%